American parishes : remaking local Catholicism - Adler, Gary J.; Bruce, Tricia Colleen; Starks, Brian (Catholic practice in North America., 2019)
Between individual Catholics and a global institution, thousands of local parishes remake Catholicism each day. With fresh data and sociological methods, this book shows how parishes are shaped by community, geography, and authority; how parishes respond to diversity and change; and how parishes worship and educate for the future of Catholicism.